A Survey on the Preference of Sustained Glaucoma Drug Delivery Systems by Singaporean Chinese Patients. Issue 7 (September 2015) - Chan, Hiok Hong; Wong, Tina T.; Lamoureux, Ecosse; Perera, Shamira
<x xml:space="preserve">Abstract</x> Purpose: To investigate the acceptance and preferences rates of 3 sustained drug delivery systems in glaucoma patients. Materials and Methods: A cross-sectional study involving 250 Chinese patients recruited from outpatient glaucoma clinics in Singapore using an interviewer-administered survey. Beliefs toward medicines, eye drops, illness perception, medication adherence, and health literacy were assessed using validated questionnaires. After receiving standard information on the 3 sustained drug delivery systems, that is, subconjunctival, intracameral, and punctal routes; each route's acceptance and attitudes were determined. Results: The subconjunctival (acceptance: 61.6%, n=154), intracameral (acceptance: 57.2%, n=143), and punctal (acceptance: 63.2%, n=158) routes were willing to be accepted by the majority of the interviewed patients. Among those, 78.6%, 79.1%, and 78.5% were willing to pay an equal or higher cost compared with their current eye drops for the subconjunctival, intracameral, and punctal plug routes, respectively. Independent factors associated with the acceptance for subconjunctival, intracameral, and punctal plug routes included: male sex (P=0.007, 0.014, 0.046, respectively), patients not on health care subsidies (P=0.022, 0.002, 0.016, respectively), and bilateral glaucoma disease (P=0.003, 0.013, 0.004, respectively). A total of 120 (48.0%) patients ranked punctal plug placement as the preferred route for sustained drug delivery followed by subconjunctival (n=76, 30.4%) and intracameral (n=54, 21.6%) routes. Conclusions: Sustained drug delivery for the medical treatment of glaucoma is an acceptable alternative to daily eye drop administration by most Singaporean Chinese individuals in this study. Male patients, nonsubsidized patients, and those with bilateral glaucoma were independently associated with preference of these 3 alternative routes of administration to traditional glaucoma drops.